CLASSICAL GUIDANCE MEETS SELF-LOVE: AN INNOVATIVE INTERVENTION TO BOOST SELF-CONFIDENCE AND SELF-IMAGE - Halimah; Saiful Muktiali (EDUCATIONE, 2026)
Self-confidence and self-image are pivotal for students’ academic engagement, persistence, and psychosocial adjustment, yet scalable classroom formats that directly strengthen these self-evaluative processes remain limited in vocational high schools. This study aimed to test the effectiveness of a brief, counselor-led, self-love–based classroom guidance module in improving self-confidence and self-image among Grade-10 students. Using a quantitative pretest–posttest control group design, two intact classes (N = 34) from an Indonesian vocational school were allocated as experimental (four sessions of self-love guidance integrating acceptance, compassionate self-talk, and mastery planning) or control (guidance-as-usual). Instruments demonstrated adequate psychometrics (item–total r = .492–.636; α = .88). The experimental group showed a large gain from pretest to posttest (M = 75.12 to 86.59; SD = 7.77 to 2.67; t(16) = –6.263, p < .001), while the control group improved modestly (M = 71.88 to 73.94; t(16) = –2.764, p = .014). Between-group effects on gains were very large (Cohen’s d = 1.61; Hedges’ g = 1.57). We conclude that a concise, classroom-deliverable self-love module can substantively elevate students’ self-confidence and self-image and reduce within-class variability, indicating convergence on adaptive coping scripts. Practically, schools can embed 10–15 minute micro-practices (reflective journaling, compassionate self-talk, if–then plans) within guidance periods without disrupting timetables. Future studies should employ larger, multi-site samples, follow-up assessments for maintenance, and mediational analyses (e.g., script internalization, self-criticism reduction) to clarify mechanisms and boundary conditions.